2020
DOI: 10.1101/2020.10.30.20222893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating the potential impact of COVID-19-related disruptions on HIV incidence and mortality among men who have sex with men in the United States: a modelling study

Abstract: Background: During the COVID-19 pandemic, gay and other men who have sex with men (MSM) in the United States (US) report similar or fewer sexual partners and reduced HIV testing and care access. Pre-exposure prophylaxis (PrEP) use has declined. We estimated the potential impact of COVID-19 on HIV incidence and mortality among US MSM. Methods: We used a calibrated HIV transmission model for MSM in Baltimore, Maryland, and available data on COVID-19-related disruptions to predict impacts of data-driven reductio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…30,33 One recent study found that even with reductions in sexual partnerships, COVID-19 restrictions would result in excess HIV-related mortality without adequate access to care. 33…”
Section: Discussionmentioning
confidence: 99%
“…30,33 One recent study found that even with reductions in sexual partnerships, COVID-19 restrictions would result in excess HIV-related mortality without adequate access to care. 33…”
Section: Discussionmentioning
confidence: 99%
“…Further details about the search results and "near misses" are in S1 section 4. We found seven modelling studies for TB [26][27][28][29][30][31][32], ten for HIV [31,[33][34][35][36][37][38][39][40][41], three for hepatitis [42][43][44] and seven for malaria [31,41,[45][46][47][48][49]. The main risk-of-bias concern was the missing uncertainty analysis, which was the case for several modelling studies.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in prevalent infections, incident HCV, incident HCC and liver related deaths over 10 years (623000, 121000, 44800, 72300)WHO region [ref. ]Global[30] AMR[39] /[40] Global (LMIC)[47] EUR[42] (United Kingdom)Type of disruptiondrop in detected cases and in detected cases treated successfully Reduced viral suppression** / reduced ART retention** Artemisinin-based therapies** (children) / Households protection (ITN or IRS)** (mothers) COVID-19 infection + service change For full results, see S1 Tables 10(TB), 11(viral hepatitis), 15-17(malaria), 22(HIV). M= months, EC = excess cases, ED=excess deaths, ITN = insecticide-treated nets, SMC= seasonal malaria chemoprevention, RR=relative risk, LMIC=low-middle income countries, ART =anti-retroviral treatment, AFR = African Region, AMR = Region of Americas, EUR = European Region, WPR = Western Pacific Region.…”
mentioning
confidence: 99%
“…This also has major implications for rates of HIV transmission throughout the duration of the crisis, where changes in income and employment have been shown to increase HIV risk 57 58. Furthermore, while this analysis did not examine the impact of COVID-19 on those living with HIV, it’s been shown that interruptions to the HIV care continuum may have impacts on community transmission, treatment, and mortality 59–62. Unless efforts are undertaken to address these disparities in access to methods of prevention, decades of progress may be lost.…”
Section: Discussionmentioning
confidence: 98%